Morbidity pattern of communicable diseases in a tertiary care hospital in metropolitan city of western Maharashtra - Kulkarni, Vrushali V.; Gurav, Nitin I.; Yadav, Amit M.; Samel, Dinesh R. (International Journal Of Community Medicine And Public Health, 2024)
Background: In India, infectious diseases continue to be predominant with emerging non-communicable diseases, imposing a double burden of diseases on health care system. Hence, the tertiary health care hospital-based study was done to compare the morbidity pattern of communicable diseases with respect to non-communicable diseases. Methods: A 2 years’ record-based data of admitted patients was collected in a tertiary health care hospital. The data was analysed using Microsoft Excel version 365. Significance of association and difference in proportions has been checked with chi-square test and Z test for SEDP respectively at significance level of 0.05. Results: During the study period of two years, 6818 patients were admitted in the hospital, of which 74.51% suffered from communicable diseases while 25.49% suffered from other types of disease including non-communicable diseases. Of the 5080, patients with communicable diseases, 57.74% were males and 42.26% were females. Communicable diseases and non-communicable diseases had male predominance (p<0.05) and was higher amongst age group 0-15 years (p<0.05). Hospital stay was prolonged in patients suffering from communicable disease (p<0.05). Significant increased difference was found in AFI, Malaria, Dengue and in Leptospirosis prevalence and significant decreased difference was found in acute gastroenteritis, IV, Covid-19, Respiratory infections and enteric fever (p<0.05). Conclusions: Communicable diseases continue to be a major threat to public health system in India. Through effective surveillance programmes, any change in trends of disease can be identified and suitable measures can be adapted to control and prevent it.